Hot Spots and Frontiers of Livestreaming Communication Research in China in the Past 10 Years—- Bibliometric Analysis and Knowledge Graph Visualization Using Cite Space - Bai , KaiGe; Tan , Kim Hua; Nor, Nur Haniz Binti Mohd; Alias, Jamsari; Mat, Norazila (Journal of Ecohumanism, 2025)
Chinese research on livestreaming communication lacks systematic theoretical analysis and comprehensive understanding; hotspots and frontiers are still unclear. Based on the relevant literature in the past ten years (2013-2023) on CNKI, this paper explores the development trends, research status, and keyword clustering in this field. It was found that academic articles on livestreaming communication in China show a significant growth trend. The past decade’s research can be divided into three stages of development, and the establishment of strong collaboration among prolific authors, represented by Yu Guoming, Liu Jia, Hua Jie, and Yan Sanjiu, remains elusive. Eight hotspots emerged in live streaming communication research during the four evolutionary phases: webcasting, livestreaming reports, mainstream media, e-commerce live streaming, sports events, media convergence, livestreaming bandwagons, and live streaming platforms. Moreover, five major research frontiers were identified: mobile live streaming, live streaming with goods, slow live streaming, live streaming with goods, and e-commerce live streaming. Regarding knowledge structure, in the cluster analysis, webcasting, e-commerce live streaming, and livestreaming coverage scale are more significant and are the current areas of concern for scholars. This study helps scholars in livestreaming communication to discover new frontiers and distinguish key knowledge subfields.